Teachers negotiating professional agency through literature‐based assessment. (14th March 2017) - Simpson, Alyson
Abstract: Research reports teachers around the world currently face major challenges to their professional agency. They face numerous pressures from accountability measures operating in the highly politicised field of literacy education and standardised testing. At the same time international research encourages teachers to design rich assessment tasks engaging students with literary texts. This paper addresses the paradox of policy working against professionalism. It is illustrated with vignettes of data to demonstrate how collective agency driven through teacher inquiry enabled a group of teachers to negotiate their professional accountability with epistemological benefits for their students. Situated in discourse supporting agentive pedagogies, the paper gives an account of a collaborative project in Australia where three primary teachers teaching students aged 10‐12 years worked with an academic research partner to investigate their own teaching practice. The paper takes a sociocultural orientation to literacy research. It examines students' responses to dialogic prompts in Literature Circles framed within a discussion that acknowledges contextual influences on teacher authority. It provides evidence of successful practice that encourages other educators to resist the power dynamics underpinning reductionist assessments of literacy achievement. The negotiation of professional agency is showcased through the teaching of literature in the classroom.